Hydrogen Sulfide Ameliorates Blood-Spinal Cord Barrier Disruption and Improves Functional Recovery by Inhibiting Endoplasmic Reticulum Stress-Dependent Autophagy - Wang, Haoli; Wu, Yanqing; Han, Wen; Li, Jiawei; Xu, Kebin; Li, Zhengmao; Wang, Qingqing; Xu, Ke; Liu, Yanlong; Xie, Ling; Wu, Jiang; He, Huacheng; et al. (Frontiers in Pharmacology, 2018)
Spinal cord injury (SCI) induces the disruption of blood-spinal cord barrier (BSCB), which elicits neurological deficits by triggering secondary injuries. Hydrogen sulfide (H2S) is a gaseous mediator that has been reported to have neuroprotective effect in the central nervous system. However, the relationship between H2S and BSCB disruption during SCI remains unknown. Therefore, it is interesting to evaluate whether the administration of NaHS, a H2S donor, can protect BSCB integrity against SCI and investigate the potential mechanisms underlying it. In present study, we found that SCI markedly activated endoplasmic reticulum(ER) stress and autophagy in a rat model of complete crushing injury to the spinal cord at the T9 level. In addition, NaHS treatment could prevent the loss of tight junction (TJ) and adherens junction (AJ) proteins both in vivo and in vitro. However, the protective effect of NaHS on BSCB restoration was significantly reduced by an ER stress activator (tunicamycin, TM) and an autophagy activator (rapamycin, Rapa). Moreover, SCI-induced autophagy was remarkably blocked by an ER stress inhibitor (4-phenylbutyric acid, 4-PBA). But an autophagy inhibitor (3-Methyladenine, 3-MA) only inhibited autophagy without obvious effects on ER stress. Finally, we had revealed that NaHS significantly alleviated BSCB permeability and improved functional recovery after SCI, and these effects were markedly reversed by TM and Rapa. In conclusion, our present study have demonstrated that NaHS treatment is beneficial for SCI recovery, indicating that NaHS is a potential therapeutic strategy for treatment of SCI.